Role Play dalam Meningkatkan Keterampilan Berbicara Siswa: Role Play dalam Meningkatkan Keterampilan Berbicara Siswa - Wiliani, Komang; Widhiasih, Luh Ketut Sri (Jurnal IKA, 2025)
This study focused on improving students’ speaking skill of 7th grade students at SMPN 14 Denpasar. In improving students’ speaking skill, the researcher conducted Classroom Action Research that consists of four stages, which are planning, action, observation, and evaluation. The preliminary observation had done in SMPN 14 Denpasar. The data was collected through reviewing students’ speaking score, observation, and conducting questionnaire. After collecting the data, the research began following stages in CAR method. The research conducted for two cycles. The research question was answered quantitatively and qualitatively. Based on the result of data analysis, it was found that the average of students’ speaking score improved from 79.5 (Pre-test) to 83.7 (Cycle 1) and 90.2 (Cycle 2). Students that passed the standard minimum passing grade also improved from 3 students (Pre-test) to 9 students (Cycle 1) and 24 students (Cycle 2). It means 87% students passed the standard minimum passing grade in Cycle 2. From the supporting data collected through questionnaire,  it is found that role play method boost their confidences, understanding the context, and improving students’ vocabulary. In conclusion, the role play method sucessfully improve students’s speaking skill.